ANALYSIS OF INFORMATION TECHNOLOGY GOVERNANCE AUDIT USING COBIT 2019 FRAMEWORK: A CASE STUDY AT GENERAL HOSPITAL DENPASAR - Sukma Paramita Sari, Ni Putu; Putu Krisna Juliharta, I Gede; Dwi Hita Darmawan, I Made (Institut Teknologi Nasional Malang, 2025)
Effective information technology management is essential for hospitals to improve efficiency and quality of service. This research evaluates information technology governance at Bhakti Rahayu General Hospital Denpasar using the COBIT 2019 framework. The problem studied was the level of process capability in achieving IT governance objectives. The toolkit design factor analysis showed five domains with a score ≥75 were evaluated, namely risk management (APO12), security management (APO13), IT change management (BAI06), disaster recovery (DSS04), and system security management (DSS05). Data was collected through a questionnaire completed by five relevant respondents. The evaluation results show that APO13, BAI06, and DSS05 are at capability level 2, while APO12 and DSS04 are at level 1 with a capability gap of 2. Proposed recommendations include implementing an Information Security Management System (ISMS) and Security Information and Event Management (SIEM) in APO12, developing a security incident SOP and information security plan in APO13, establishing a cross-departmental team and documenting change requests in BAI06, improving security infrastructure in DSS04, and implementing cloud computing such as software as a service (SaaS) to save operational costs and increase flexibility in DSS05.